DIRECTIONS OF DIVERSIFICATION OF RURAL DEVELOPMENT IN THE CONDITIONS OF DECENTRALIZATION (INNOVATIVE ECONOMY, 2019)
Khomiuk N.L. DIRECTIONS OF DIVERSIFICATION OF RURAL DEVELOPMENT IN THE CONDITIONS OF DECENTRALIZATIONPurpose. The aim of the article is determining the areas of diversification of rural development in decentralization in order to improve the quality of life of rural population and ensure the competitiveness of rural areas and achieve environmental security.Methodology of research. Common methods of study are applied in economic science in the course of the study, in particular: monographic, system and structural - in determining the directions of diversification of rural development in the conditions of decentralization.Findings. The following areas of diversification of rural development under decentralization conditions have been identified in order to ensure the social and ecological and economic development of rural territories: diversification of agricultural production; diversification of non-agricultural activities; diversification of funding sources; diversification of forms of ownership and management. It is suggested to diversify the development of rural territories in the field of agricultural production by expanding the range of products, increasing the volume of organic and niche production.It is determined that the choice of non-agricultural activities for each rural area is different and depends on natural resources and its location. The directions of diversification of non-agricultural activity in rural areas are proposed, such as: industry, rural green tourism, services and folk arts, production of specific regional products, legal entities and individuals, grants. We believe that the diversification of ownership and management in rural areas involves stimulating the development of different forms of ownership, promotion of various forms, creation of cooperatives and clusters.Originality. The scientific and practical recommendations on the formation of directions of diversification of rural development under decentralization conditions, which are determined depending on the object of diversification (agricultural production, non-agricultural activity, sources of financing, forms of ownership and management), have been improved.Practical value. The obtained results of the study are the basis for solving practical problems of rural development in the context of decentralization in Ukraine.Key words: diversification of rural development; agricultural production; non-agricultural activities; sources of financing; ownership and economic management; organic production; cluster.
Keywords: Key words; diversification of rural development; agricultural production; non-agricultural activities; sources of financing; ownership and economic management; organic production; cluster.